2014
DOI: 10.1002/anie.201406103
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Wittig Reactions of Semi‐ and Nonstabilized Ylides Enabled by Ylide Tuning

Abstract: The first examples of catalytic Wittig reactions with semistabilized and nonstabilized ylides are reported. These reactions were enabled by utilization of a masked base, sodium tert-butyl carbonate, and/or ylide tuning. The acidity of the ylide-forming proton was tuned by varying the electron density at the phosphorus center in the precatalyst, thus facilitating the use of relatively mild bases. Steric modification of the precatalyst structure resulted in significant enhancement of E selectivity up to >95:5, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 37 publications
0
50
0
1
Order By: Relevance
“…These problems can be eliminated by applying the phosphine in a catalytic amount, and by insuring the in situ reduction of the phosphine oxide formed. This was first elaborated for the Wittig reaction using silanes as the reducing agent by O'Brien . Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications .…”
Section: Introductionmentioning
confidence: 99%
“…These problems can be eliminated by applying the phosphine in a catalytic amount, and by insuring the in situ reduction of the phosphine oxide formed. This was first elaborated for the Wittig reaction using silanes as the reducing agent by O'Brien . Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications .…”
Section: Introductionmentioning
confidence: 99%
“…It has been a challenge to develop catalytic versions of these reactions involving the recycling of the waste cyclic phosphine oxides in in situ reduction [6]. O wide range of phosphine oxides including mainly phospholene-and phospholane derivatives [7][8][9][10]. In these cases, the phosphoranes were formed in situ by the quaternization of the phosphine by the α-haloacetic ester [7][8][9] or even an unactivated alkyl halide [8], followed by dehydrohalogenation by Na 2 CO 3 [7,9], diisopropylethylamine [8], or in situ generated t BuONa [10].…”
Section: Introductionmentioning
confidence: 99%
“…C 2014 Wiley Periodicals, Inc. Heteroatom Chem. It was found that the deoxygenation with TMDS or PMHS under MW and solvent-free conditions may be the method of choice and provides a green chemical approach.…”
mentioning
confidence: 99%
“…In recent years, though, several new catalytic methods involving cycling through phosphine oxide intermediates have emerged, 5 both in redox-neutral 67, and redox-driven modes. 810 As part of a program aimed at developing designer main group compounds as broadly useful biphilic 11 catalysts in organic synthesis, 12 we recently reported the use of phosphetanes as O -atom transfer catalysts operating via P III /P V =O redox cycling. 12c In this Communication, we advance this biphilic catalysis concept by describing a catalytic N - N bond forming heterocyclization enabled by phosphetane-catalyzed reductive O -atom transfer.…”
mentioning
confidence: 99%